A Contribution to Sustainable Development in ASEAN: German FDI in Vietnam's Energy Sector - Stoffers, Andreas; Fuchs, Benno (AEI Insights, 2021)
With its enormous economic growth rate of an average 6% p.a. over the last 15 years, ASEAN has emerged to be one of the most vibrant and promising regions in the world. Long before the inauguration of the ASEAN Economic Community (AEC) in 2015, the European Union’s economy in general and Germany’s in particular, has realized the potential of Southeast Asia as an outlet, trading partner, and production base. Besides bilateral relations, regional economic zones like ASEAN, EU and NAFTA as well as multinational agreements like TPP and TTIP are gaining ground. At the same time, the hunger for energy is rising in line with the economic boom, even exceeding the latter rates. In order to meet the rising demand ASEAN will be increasingly focused on sustainable energy. In this article, the opportunities for sustainable energy supply in ASEAN are assessed, based on the example of Germany and Vietnam and the background of global and regional economic integration. Due to the limited space in this article, the authors focus on the positive aspects of the German-Vietnamese cooperation being well aware that there are also other bilateral relationships worthwhile to investigate. Furthermore, there is the need to have in mind that there are also pitfalls and alternatives, which needs to be discussed in a follow-up article.